Determinants of Psychological Health among Shipyard Workers: A Literature Review - Rika Yulianti Fitri; Mutia Permata Iryanti; Trisna Jayati (SEAN Institute, 2026)
Psychological health is an important occupational health issue among shipyard workers, who may be exposed to multiple physical, environmental, psychosocial, and organizational demands. However, evidence regarding the determinants of psychological health in this occupational group remains fragmented. This literature review aimed to identify and synthesize evidence on organizational, psychosocial, environmental, work-related, and individual factors associated with psychological health and related work outcomes among shipyard workers. A literature review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. Literature searches were performed in Google Scholar, PubMed, and ProQuest in July 2026 using English and Indonesian keywords. Studies published between 2016 and 2026 were screened based on predefined inclusion and exclusion criteria. Eleven original research articles were included and descriptively synthesized. The findings indicated that psychological health among shipyard workers was associated with multiple determinants, including safety climate, supervisor support, organizational roles, career development, workload, psychological demands, social support, work–life balance, noise exposure, job control, environmental risks, time perspective, age, and education. These factors were associated with work stress, burnout, psychological strain, job satisfaction, organizational commitment, absenteeism, presenteeism, and safety performance. In conclusion, psychological health among shipyard workers is multifactorial and requires comprehensive occupational health strategies integrating workplace hazard control, organizational support, improved work design, and psychosocial interventions.